All that Trash : the Story of the 1987 Garbage Barge and Our Problem with Stuff - McCarthy, Meghan (New York : Simon & Schuster Books for Young Readers, 2018)
"The true story of a garbage barge that didn't have a place to dock-- and was one of the events that led to the recycling movement."--Provided by publisher.
"A Paula Wiseman Book."
Accelerated Reader AR
Keywords: Mobro 4000 (Barge) -- Juvenile literature; Break of Dawn (Tugboat) -- Juvenile literature; Barges -- Juvenile literature. -- United States; Refuse and refuse disposal -- Juvenile literature. -- United States; Voyages and travels -- Juvenile literature; Sea stories -- Miscellanea; Islip (N.Y.) -- Juvenile literature. -- History -- 20th century